2003
DOI: 10.1021/om030439a
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Lanthanide Alkyl and Amide Precatalysts Efficiently Mediate Intramolecular Hydrophosphination/Cyclization. Observations on Scope and Mechanism

Abstract: Supporting InformationMaterials and Methods. All manipulations of air-sensitive materials were carried out with rigorous exclusion of oxygen and moisture in flame-or oven-dried Schlenk-type glassware on a dual-manifold Schlenk line, or interfaced to a high-vacuum line (10 -6 Torr), or in a nitrogenfilled Vacuum Atmospheres glovebox with a high capacity recirculator (< 1 ppm of O 2 ). Argon (Matheson, prepurified) was purified by passage through a MnO oxygen-removal column and a Davison 4A molecular sieve colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(54 citation statements)
references
References 17 publications
1
53
0
Order By: Relevance
“…Corresponding second-order dependences on the substrate concentration have only been reported for selected examples of rare-earth-metal-catalyzed intramolecular hydroamination [9] and hydrophosphination reactions. [10] On the other hand, comparable kinetic studies performed with two ansaZr catalysts suggested a zero-order dependence on the substrate concentration.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Corresponding second-order dependences on the substrate concentration have only been reported for selected examples of rare-earth-metal-catalyzed intramolecular hydroamination [9] and hydrophosphination reactions. [10] On the other hand, comparable kinetic studies performed with two ansaZr catalysts suggested a zero-order dependence on the substrate concentration.…”
Section: Resultsmentioning
confidence: 90%
“…However, second-order dependences on the substrate concentration have been described for selected examples of rare-earthmetal-catalyzed intramolecular hydroamination [9] and hydrophosphination reactions. [10] Although the results obtained for the formation of piperidines catalyzed by Ti(NMe 2 ) 4 , Ind 2 TiMe 2 , Ind 2 ZrMe 2 and Ind 2 HfMe 2 suggest that for these reactions Ti catalysts show increased catalytic activity compared with the corresponding Zr catalysts, the formation of aminocyclopentane side-products by C-H activation processes was found to be a severe drawback of the Ti catalysts. Fortunately, these side-products are not formed in Ind 2 ZrMe 2 -and Ind 2 HfMe 2 -catalyzed reactions.…”
Section: Discussionmentioning
confidence: 96%
“…GC-MS analyses were carried out on an Agilent 6890/Micromass GCT-MS instrument. 1 H NMR and 13 C NMR spectra for analyses of compounds were recorded on a Bruker DPX-300 NMR spectrometer in pyridine-d 5 for lanthanide complexes and in CDCl 3 for organic compounds and polymers, and chemical shifts for 1 H and 13 C NMR spectra were referenced to internal solvent resonances. Gel permeation chromatography (GPC) analyses of polymer samples were carried at 30°C using THF as an eluent on a Waters-150C instrument and calibrated using monodispersed polystyrene standards at a flow rate of 1.0 mL min À1 .…”
Section: Methodsmentioning
confidence: 99%
“…238 Further studies have been reported of the intramolecular hydrophosphination/cyclisation of primary phosphino-alkynes and -alkenes to form cyclic phosphines in the presence of organolanthanide complexes. 239 Diphenylphosphine has been shown to add diastereoselectively to benzaldimines coordinated to a chromium tricarbonyl acceptor, to form complexed chiral aminoalkylphosphines. 240 The synthesis of P-chiral functionalised secondary phosphines by addition of iron-complexed primary phosphines to alkenes and alkynes has been reviewed.…”
Section: Preparation Of Phosphines By Addition Of P-h To Unsaturatedmentioning
confidence: 99%